2013
DOI: 10.1007/s11164-013-1335-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of antibacterial 2-(pyridin-3-yl)-1H-benzo[d]imidazoles and 2-(pyridin-3-yl)-3H-imidazo[4,5-b]pyridine derivatives

Abstract: The increasing clinical importance of drug-resistant fungal and bacterial pathogens has stimulated microbiological research into and development of new antimicrobial agents. Hence, in this study, we synthesized novel series of 2-(pyridin-3-yl)-1H-benzo[d]imidazoles and 2-(pyridin-3-yl)-3H-imidazo[4,5-b]pyridine derivatives. The structures of the compounds were confirmed by spectral and CHN analysis. The compounds were examined for in-vitro antimicrobial activity against Gram-positive bacteria (Staphylococcus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…All the samples show antifungal activity against C. The results further confirmed that triazole groups grafted into the synthesized chitosan derivatives contribute a lot to the antifungal action and consequently increase the antifungal activity of them. The triazole groups could inhibit synthesis of the cell membrane and cell wall to exhibit antimicrobial activity [39]. At the same time, the inhibitory index of TCTS with DS of 0.86% was slightly inferior to that of CTCTS with DS of 0.78 and BTCTS with DS of 0.82, suggesting that a higher inhibitory index of CTCTS and BTCTS should be possible if TCTS, CTCTS, and BTCTS have the same DS.…”
Section: Water Solubility and Antifungal Activitymentioning
confidence: 99%
“…All the samples show antifungal activity against C. The results further confirmed that triazole groups grafted into the synthesized chitosan derivatives contribute a lot to the antifungal action and consequently increase the antifungal activity of them. The triazole groups could inhibit synthesis of the cell membrane and cell wall to exhibit antimicrobial activity [39]. At the same time, the inhibitory index of TCTS with DS of 0.86% was slightly inferior to that of CTCTS with DS of 0.78 and BTCTS with DS of 0.82, suggesting that a higher inhibitory index of CTCTS and BTCTS should be possible if TCTS, CTCTS, and BTCTS have the same DS.…”
Section: Water Solubility and Antifungal Activitymentioning
confidence: 99%
“…The antibacterial activity of successive extracts was performed using agar cup-plate method (Mallemula et al, 2013). Twenty milliliter of the sterile nutrient agar medium was poured into sterile Petri-dishes and allowed to solidify.…”
Section: Anti-microbial Activitymentioning
confidence: 99%
“…It is known that 1,2,3-triazoles are antimicrobial agents per se, because they can inhibit synthesis of the cell membrane, cell wall, and nucleic acids of bacteria [35]. The antimicrobial action is generally caused by ionic and hydrophobic interactions between the biocide and the outer phospholipid membrane of the microorganism [40].…”
Section: Antimicrobial Activitymentioning
confidence: 99%